A production and operations management study of Johnson and Johnson (Phils.), Inc. Liquid Line - Aquitania, Aries Alexander E. (College of Engineering, 1997)
Johnson & Johnson is a U.S. corporation organized in 1886 with headquarters in New Brunswick, New Jersey. The corporation is engaged in the manufacture and marketing of a broad range of products in the health care field which include baby and adult toiletries, feminine hygiene, oral and wound care products, as well as professional, diagnostic and pharmaceutical products. For the purposes of this study, the group focused on the Liquid Line of the company, this includes cologne, oil and lotion. The study is limited to these 4 variants of cologne: Regular, Brisa, Floral and Fresh Blossom; as well as its different sizes. For the Regular cologne, there?s 25, 50, 125 and 300 mL. as for Brisa, Floral and Fresh Blossom, there?s: 25, 50 and 125 mL were considered. For the oil products, the group considered its two products; namely: Baby Oil and Oil with Powder Scent. The former comes in 4 sizes: 25, 50, 125 and 300 mL. The lotion line also consists of two products: namely: Lite lotion and the Rich & Creamy lotion. Both of these products come in 3 sizes: 50, 125 and 200 mL. During the course of the study, the group noticed that the company does not use any long term forecasting. As a result, the company does not have any capacity planning for the coming years. The company merely opts to plan its capacity for the present year. At present, the manufacturing firm cannot meet the demand for its products. Therefore, the group decided to use aggregate planning in order to find some option that will allow the company to meet the its future demand, as well as give the company the least cost. Given the annual unit sales per sku for the past five years (1992-1996), forecast for the demand of the coming years (1997-2001) were generated using the Linear Regression Method. These forecasted values became the basis for the capacity planning and eventually the aggregate planning of the liquid production plant. The group came up with several alternatives in order for the company to meet its future demand. These are: ? The present system with overtime ? 3 shifts for the Kalish and 3 shifts for the High Speed ? 3 shifts for the Kalish and 3 shifts for the High Speed and utilize overtime ? Purchase a new Kalish: 2 shifts for the Kalish and 2 shifts for each High Speed ? Purchase a new High Speed: 2 shifts for the Kalish and 2 shifts for each High Speed ? Purchase a new High Speed: 2 shifts for the Kalish and 2 shifts for each High Speed with utilize overtime ? Purchase a new High Speed: 2 shifts for the Kalish and 3 shifts for each High Speed ? Purchase a new High Speed: 2 shifts for the Kalish and 3 shifts for each High Speed with utilize overtime ? Purchase a new High Speed: 3 shifts for the Kalish and 2 shifts for each High Speed ? Purchase a new High Speed: 3 shifts for the Kalish and 2 shifts for each High Speed with utilize overtime After evaluating the alternatives, it was considered that it was in the best interest of the company to employ a third shift for its Kalish machine as well as work overtime in order to meet the demand for this year. This alternative will give the company an annual cost of about P310M while generating income due to lost sales of about P73M. It was also determined that the recommended setup will remain feasible up to the year 2001.